Woman's contraceptive needs and preferences in the postpartum period: an Italian study. Issue 23 (December 2013) - Di Giacomo, Patrizia; Sbarlati, Alessia; Bagnasco, Annamaria; Sasso, Loredana
Abstract : Aims and objectives: To describe what puerperal women know about postpartum contraception and to identify their related needs and expectations. Background: Puerperal women face the problem of beginning or resuming contraception, the choice of the right method of contraception and the right time to start it. This choice becomes particularly important in case they breastfeed since the contraceptive method should not interfere with breastfeeding. Different factors, such as the level of knowledge women have about various contraceptive methods, their individual preferences or their desire to have a baby, can strongly influence this choice. Design: A cross‐sectional study had been carried out within the period of six months, from November 2011–February 2012. Methods: Three hundred puerperal women were interviewed before their discharge from a Maternity Home. The women were asked for their personal characteristics, their maternity history, the information they had received, their knowledge and expectations about postpartum contraception and their intention to use contraception. Results: During pregnancy and postpartum, 45·5% of the women reported that they had received adequate information about contraception. Of these ones, 64·3% reported their intention to use contraception either to avoid pregnancy or to space out future births, even if they did not always have appropriate knowledge about fertility and the use of contraceptive methods during postpartum. During this study, we also discovered that women's intention to use contraception was proportional to their level of education. Conclusion: Women need more and appropriate information about postpartum contraception, to make a conscious choice in relation to their needs and without putting their health at risk. Relevance to clinical practice: To promote awareness of the choices related to postpartum contraception, it is important to understand the personal characteristics that influence or hinder this choice. Midwives can play a very important role in informing women and in developing educational interventions to support a safe contraceptive choice.